Signalling Expertise in Sport Entrepreneurship: A Mixed-Methods Approach Using Topic Modeling and Thematic Analysis - Ted Hayduk; Brianna Newland (Journal of Applied Sports Management, 2020)
Despite the recent importance of technological entrepreneurship to sport business, very little is known about the entrepreneurs who are actively defining this new landscape. And, given that effective communication is essential to a thriving entrepreneurship ecosystem, it is important for investors to understand who sport entrepreneurs are and how they position themselves to the world. This will help create a sport business landscape that is receptive to new technologies and supportive of the entrepreneurs who champion them. Thus, the purpose of this paper is to illuminate how sport entrepreneurs communicate with potential investors. To do so, the paper employs a mixed-methods approach, using a natural language processing algorithm to decipher themes in the entrepreneurs’ self-reported biographies, followed by a qualitative investigation that uncovers how each theme was leveraged.
Keywords: Business; Communication; Finance; Investing; Relationships; Technology